« Faire public au théâtre aujourd’hui » - Dominique Pasquier (Terrains/Théories, 2017)
How to perform as a public in a theater ? This article, based on interviews with 80 spectators, analyzes their relationship to actors and other spectators during the shows. There is a consensus on respect for the work of the actor and an overall acceptance of the standards of behavior expected in a theater. Nevertheless, negative reactions to a show can give some spectators physical manifestations of disengagement from the situation, sometimes uncontrollable, sometimes voluntary. We can distinguish between deviations from the rule that are perceived as a breakdown of the interaction and those that are considered acceptable because they are part of "backstage" practices, in the Goffmanian sense of this term. Making public in a theater is therefore the result of a set of compromises to maintain a fragile interactional situation.